The Behavioral Analysis in the Critical Infrastructure (The Influence of Covid-19) - Kaleeva, Tiana (Research Papers, 2022)
The aim of the current article is to outline the behavioural analysis as an instrument for improvement of the security, emphasizing on its role in the critical infrastructure locations. Based on documentary and comparative analysis various technologies and programs based on behavioral analysis are being presented, and in this way, illustrates not only their operating mechanisms and benefits but also the development trends in this sphere. Multiple and diverse challenges for the behavioral analysis caused by the impact of the Covid-19 crisis are also presented. Possible solutions for overcoming them are proposed taking into an account the different financial and resource factors.